The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s10051-001-8706-1
|View full text |Cite
|
Sign up to set email alerts
|

Coherent transport in disordered metals out of equilibrium

Abstract: We derive a formula for the quantum corrections to the electrical current for a metal out of equilibrium. In the limit of linear current-voltage characteristics our formula reproduces the well known Altshuler-Aronov correction to the conductivity of a disordered metal. The current formula is obtained by a direct diagrammatic approach, and is shown to agree with what is obtained within the Keldysh formulation of the non-linear sigma model. As an application we calculate the current of a mesoscopic wire. We find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 25 publications
(64 reference statements)
0
22
0
Order By: Relevance
“…ρ and Φ depend on the details of the device under consideration and we will come back to them below. The expression for the correction to the current in the wire has been obtained diagrammatically in [14] and is given by…”
mentioning
confidence: 99%
“…ρ and Φ depend on the details of the device under consideration and we will come back to them below. The expression for the correction to the current in the wire has been obtained diagrammatically in [14] and is given by…”
mentioning
confidence: 99%
“…We now consider the other two limits, b) and c). We found that in both limits the current can be written as [54] δI…”
Section: Non-linear Conductivity In Wiresmentioning
confidence: 96%
“…The expression for the current density (113) has been derived first in [54], both using diagrammatic techniques as well as with the Keldysh version [51,52,125] of the non-linear sigma model [46]. Eq.…”
Section: Interaction Correction To Diffusive Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…To be specific, we consider a weakly disordered quasi-1D metallic wire of length L in the out-ofequilibrium situation. At small voltage V , the quantum interaction correction to the classical result I class = (2 s e 2 V /h) g is 22,23 : ∆I(V ) (2 s e 2 V /h) (L T /L) − 1.57 + 0.067 (eV ) 2 E Th /(k B T ) 3 , where E Th = D/L 2 is the Thouless energy of the wire. The first term is the well-known Altshuler-Aronov correction [19][20][21]24,25 , dominated by exchange (Fock contribution) for weak screening.…”
Section: Introductionmentioning
confidence: 99%